Peluang dan tantangan Bandar Udara Internasional Jawa Barat (BIJB) Kertajati sebagai pusat pertumbuhan ekonomi baru - Arinda, Naila Salma; Zid, Muhammad; Saputro, Hikari Dwi Saputro; Yusuf, Muhammad (Prosiding Seminar Nasional Pendidikan, Ilmu-Ilmu Sosial, dan Hukum (SENPISHUM), 2026)
West Java International Airport (BIJB) Kertajati is a national strategic project designed as a new economic growth center in eastern West Java. However, to date, its contribution to the regional economy remains limited, as indicated by low flight activity and slow development of the aerocity area, thus demonstrating a gap between planning and the realization of economic impact. This study aims to identify the economic opportunities and challenges of BIJB Kertajati based on the experiences of other airports in Indonesia and the aerotropolis concept approach. The method used is a systematic literature review focusing on studies of airport development, aerocity development, and regional economic impact. Data were obtained from relevant journal articles and policy reports, then analyzed through a process of identification, comparison, and synthesis of findings across studies. The results of the study show that the opportunities for BIJB Kertajati include strengthening logistics connectivity through the Cisumdawu Toll Road and Patimban Port, developing an integrated aerocity, creating jobs, and opportunities for the adoption of technology-based industries. Meanwhile, the main challenges include low airport operational performance, limited local community participation, investment policy uncertainty, and slow development of supporting infrastructure. This study concludes that optimizing the role of BIJB Kertajati requires an collaborative approach that integrates economic, social, and environmental aspects to promote sustainable regional economic growth.